"Your network bandwith is low": Online Participatory Music-Making in the COVID-19 Era - Morgan-Ellis, Esther M. (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
My contribution is a personal account about my experiences with online participatory music-making in the first few months of the pandemic. As an old-time fiddler, I anchored a local Zoom jam and attended a Zoom-based music camp. As a Sacred Harp singer, I participated in regular singings via Facebook Live.